Study Of The Efficacy, After Giving Equal Bolus Dose Of 8ml Of Ropivacaine 0.1% Vs Ropivacaine 0.2% With Fentanyl For Post-Operative Patient-Controlled Epidural Analgesia In Patients Undergoing Infra- Umbilical Abdominal Surgery And Lower Limb Orthopedic - K. Harini; Vaishalee Ketan Badhe; Manisha Phulbone; Vaijayanti Badhe; Ketan Badhe (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Epidural analgesia is widely accepted as the prime modality of providing optimal post-operative analgesia after major surgery, and patient-controlled epidural analgesia (PCEA) has recently gained popularity. It is often used in the post-operative phase and can be given as boluses, infusions, or a combination of the two. Local anesthetic has been used as the mainstay for epidural analgesia, alone or in combination with opioids. Ropivacaine is a relatively new amino amide local anesthetic, with Fentanyl is the opioid often used. Aims and Objectives: To study the efficacy, after giving 8ml bolus dose of ropivacaine 0.1% versus 0.2% with fentanyl for postoperative patient-controlled epidural analgesia in patients undergoing infra-umbilical abdominal and lower limb orthopedic surgery at Pravara Rural Hospital, Loni. Materials & methods: 74 patients were included in the study where the patients were divided into two groups with Group 1 given Ropivacaine 0.1% with Fentanyl 2 µg/ml and Group 2 given Ropivacaine 0.2% with Fentanyl 2 µg/ml. The PCEA pump will be programmed to deliver a continuous epidural infusion at the rate of 8 ml/hour after the initial 8 ml bolus dose, with a PCEA bolus dose of 4 ml and lockout interval of 20 minutes. Postoperatively the intensity of pain by vas score, degree of motor blockade, level of sedation, the total volume of drug infused, variation in hemodynamic parameters, and adverse effects were observed. Results: Group 1 reported a mean VAS, significantly higher than Group 2’s mean VAS. Overall, the data suggest that Group 1 consistently experiences higher VAS scores compared to Group 2 across the measured time intervals, indicating potentially differing levels of perceived discomfort or pain between the two groups. Conclusion: Ropivacaine 0.2% with fentanyl is more efficacious than Ropivacaine 0.1% with fentanyl when used as PCEA in the postoperative period for analgesia.